Family Business and Regional Development - Basco, Rodrigo; stough, Roger; Suwala, Lech (Taylor & Francis, 2021)
" This book explores the relationship between families, firms, and regions and the extent to which these relationships contribute to regional economic and social development. Although family business participation in economic activities has been a common phenomenon since pre-industrial societies, and its importance has evolved throughout time and across spatial contexts, the book suggests that these factors have often been neglected in family business and regional studies. Taking this research gap into account, the book aims to deepen our understanding of the role family firms play in the regional economy. In particular, it explores two seldom studied questions. Firstly, what role do family firms play in regional development? Secondly, how do formal and informal regional contexts shape family firm operations and performance? This book presents a model of ""regional familiness"" and uses themes such as productivity, networks and competitiveness to shed new light on family businesses. Moreover, it evaluates the juxtaposition and cross-fertilisation between family business and regional studies to encourage the cross-fertilisation of ideas, theories, and research methods between the two fields. Bringing together leading experts in entrepreneurship, regional economics and economic geography, this book will be valuable reading for advanced students, researchers and policymakers interested in family firms, regional studies and economic geography."